International Fragmentation of Tradable Business Services: the Case of Hungary - Magdolna Sass (Hungarian Academy of Sciences, Institute of Economics, 2010)
Hungary is increasingly appearing on the map of trade in services. This is mainly due to the appearance of foreign owned shared services centres, regional or even global headquarters of multinationals. First, data problems are listed in detail when analysing tradable services (applying, extending and analysing in-depth the problems indicated by Kirkegaard, 2005). It draws the conclusion that using available statistical data on trade and FDI is misleading in trying to assess the extent of Hungary's participation in the international division of labour in services. Moreover, lack of data hinders the analysis of other aspects. That is why the paper relies on detailed company case studies (8 companies interviewed in 2008 out of around 50 such centres in Hungary). Two aspects of export oriented services projects are analysed in detail: locational advantages of Hungary which attract such projects to the country and the impact of these projects on the host economy. Vertical FDI associated with this type of efficiency seeking and highly export oriented projects, has completely different localisation requirements and local impact than horizontal FDI, which up till around 2000 dominated services FDI inflows in Hungary. As an analytical framework, Barba Navaretti, Venables, 2004 is used. The paper identifies the various elements of locational advantages connected to different elements of investment motives, in terms of cost reduction, reducing costs of disintegration of production, reducing other costs, and motives arising from the confluence of vertical and horizontal FDI, and relates these elements to the specificities of the business services sector. It differentiates general motives, which play a role in compiling the "longer list" of possible investment locations and motives which play the most important role in deciding about the final location of the investment. Analysis of Hungary is supplemented with a comparison with the other three Visegrad countries. The paper also presents the most important channels through which FDI in business services may affect the host country. The analysis is based on theories, dealing mainly with the impact of manufacturing FDI, and especially of vertical FDI on the host economy (e.g. Dunning, 1993, Lall, 1980, Blomstrm, Kokko, 1997, Barba Navaretti, Venables, 2003, Caves, 2007), taking 3 into account specificities of business services. The paper identifies the following areas in which business services FDI impacts upon the host economy: job creation (type of activities and categories of employees affected), backward and forward linkages with local companies and with other local actors, and other spillovers (impact on the business environment and infrastructure, spillovers through trained employees).
Keywords: F21; F23; L8; 330; offshore outsourcing; business services; locational advantages; local impact; Hungary; East Central Europe; Unternehmensdienstleistung; Auslandsverlagerung; Outsourcing; Auslandsinvestition; Wirkungsanalyse; Ungarn